Study Of Wound Healing In Rats Treated With Skin Of Poisonous Frog, Odorrana Hosii - Rasit, AH (UTM Press, 2015)
A grafting techniques or using various synthetic and biological dressing also widely used to protect the wound area. There are 8 peptides with differential antimicrobial activities contained in Odorrana hosii’s skin secretion. However, to our best knowledge no study has been scientifically conducted to reveal the value off this species on wound healing. Primarily, the aim of this study was to look at the potential use of O. hosii’s skin as a biological dressing in wound healing management. This study assessed the wound healing in rat compared between wound grafted with O. hosii’s skin and wound treated with normal saline dressing. Histological examination was done to assess the wound healing activities after 14 days. The result shown, both wounds which were treated with O. hosii’s skin and untreated wound heal completely on day 14 as the epidermis and dermis completely close. Histologically, the percentage of neutrophils, macrophages and fibroblasts, were reduced on day 14. However, wounded skin, which was treated with O. hosii’s skin, had better healing quality as more new tissues and hair follicle regrowth compared with the untreated wound. It is suggested that poison gland in the O. hosii’s skin did not harm the wounded rat skin, instead, poison that act as defensive mechanism can help the species to fight the pathogen on the wound.